Positive electrode slurry, positive electrode plate, lithium ion battery and electric device

By using high-specific meter conductive carbon black and carbon nanotubes in the positive electrode slurry and filling with porous additives to form a multi-stage gradient pore structure, the problem of battery energy density decline caused by the increase in the proportion of conductive agents is solved, and the fast charging capacity, cycle life and low-temperature discharge capacity of the battery are significantly improved.

CN119650699APending Publication Date: 2025-03-18ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411812753.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, due to the increase in the proportion of conductive agent, the energy density of the battery decreases, destroying the overall performance of the battery.

Method used

A positive electrode slurry is used, including lithium iron phosphate main material, binder, conductive agent and porous additive, wherein the conductive agent includes conductive carbon black and carbon nanotubes with high specific meter. By filling medium and small pore diameter pore additives and high specific meter carbon black, a multi-stage gradient pore structure is formed to improve the lithium ion transmission efficiency.

Benefits of technology

It effectively improves the local liquid retention capacity, fast charging capacity, cycle life and low-temperature discharge capacity of the battery, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_8
    Figure SMS_8
  • Figure SMS_9
    Figure SMS_9
  • Figure SMS_10
    Figure SMS_10
Patent Text Reader

Abstract

The invention provides positive electrode slurry, a positive electrode plate, a lithium ion battery and a power utilization device, a positive electrode lithium supplement agent comprises a lithium iron phosphate main material, a binder, a conductive agent and a porous additive, the conductive agent comprises conductive carbon black with a high specific surface area, and the specific surface area of the conductive carbon black is greater than or equal to 130 m < 2 > / g. The space between the lithium iron phosphate particles in the positive electrode slurry provided by the invention is filled with the porous additive with the medium aperture and the conductive carbon black with the small aperture and the high specific surface area, so that a positive electrode plate applying the positive electrode slurry not only is small in internal pore spacing, but also forms gradient pore structure matching capable of reducing tortuosity of lithium ion transmission, and the lithium ion transmission efficiency is improved. And the technical effects of improving the electrolyte wettability of the electrode, improving the quick charge capacity, the cycle life, the low-temperature discharge capacity and the like of the battery are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a positive electrode slurry, a positive electrode sheet, a lithium ion battery, and an electrical device. Background Art

[0002] With the rapid development of the lithium battery industry, the demand for batteries with high fast charging capability and long cycle life is more urgent. In order to meet market demand, battery performance is usually improved by adjusting the cathode slurry formula and changing the electrode structure.

[0003] In the prior art, the amount of conductive agent in the positive electrode slurry formula is often increased to improve the local liquid retention capacity of the battery electrode, the fast charging capacity and the battery cycle capacity.

[0004] However, due to the increase in the proportion of conductive agent, the content of iron-lithium main material in the formula will also decrease, which will lead to a decrease in battery energy density, thereby destroying the overall performance of the battery. Summary of the invention

[0005] The present invention provides a positive electrode slurry, a positive electrode plate, a lithium ion battery, and an electrical device, which can effectively improve the local liquid retention capacity, fast charging capacity, cycle life, and low-temperature discharge capacity of the battery plate, and effectively overcome the defects in the prior art.

[0006] In a first aspect of the present invention, a positive electrode slurry is provided, comprising: a lithium iron phosphate main material, a binder, a conductive agent and a porous additive, wherein the conductive agent comprises a conductive carbon black with a high specific surface area, and the specific surface area of ​​the conductive carbon black is ≥130m 2 / g.

[0007] According to one embodiment of the present invention, the conductive agent further includes carbon nanotubes compounded with conductive carbon black.

[0008] According to one embodiment of the present invention, the carbon nanotubes are multi-walled carbon nanotubes, wherein the specific surface area of ​​the multi-walled carbon nanotubes is 230-420 m 2 / g, tube diameter is 7~11nm.

[0009] According to one embodiment of the present invention, the tap density of the conductive carbon black is ≤0.05 g / cm 3 .

[0010] According to one embodiment of the present invention, the average particle size of the primary structure of the conductive carbon black is 20-30 nm.

[0011] According to one embodiment of the present invention, the porous additive is porous alumina.

[0012] According to one embodiment of the present invention, the specific surface area of ​​porous alumina is 320-360 m 2 / g, and the porous alumina has a pore size distribution of 30-150 nm.

[0013] According to one embodiment of the present invention, the primary particle size of the porous alumina is 80 nm ≤ D 50 ≤120nm.

[0014] According to one embodiment of the present invention, the average primary particle size of the porous alumina is 60 nm.

[0015] According to one embodiment of the present invention, the primary particle size of the lithium iron phosphate main material is in the range of 280-340 nm, and the particle size of the lithium iron phosphate main material satisfies 2.8≤(D 90 -D 10 ) / D 50 ≤3.2.

[0016] According to one embodiment of the present invention, polyvinylidene fluoride.

[0017] According to one embodiment of the present invention, the pore size of the conductive carbon black is 5-30 nm, and the average pore size of the conductive carbon black is 5-9 nm.

[0018] According to one embodiment of the present invention, the primary structure particle size of the conductive carbon black is 60≤D 50 ≤82nm.

[0019] A second aspect of the present invention provides a positive electrode plate, comprising: a positive electrode current collector and a positive electrode coating coated on the surface of the positive electrode current collector, wherein the positive electrode coating comprises the positive electrode slurry in the above-mentioned first aspect and / or various possible embodiments of the first aspect.

[0020] A third aspect of the present invention provides a lithium-ion battery, comprising the positive electrode sheet of the second aspect.

[0021] A fourth aspect of the present invention provides an electrical device comprising the lithium-ion battery of the third aspect.

[0022] The implementation of the present invention has at least the following beneficial effects:

[0023] The lithium iron phosphate particles in the positive electrode slurry are filled with medium-pore porous additives and small-pore high-specific surface area conductive carbon black. The positive electrode sheet using this positive electrode slurry not only has a small pore spacing inside, but also forms a gradient pore structure that can reduce the tortuosity of lithium ion transmission, achieving the technical effect of improving the electrolyte wettability of the electrode and improving the battery's fast charging capability, cycle life and low-temperature discharge capability. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0025] Based on the above technical background, the first aspect of the present invention provides a battery slurry, including a lithium iron phosphate main material, a binder, a conductive agent and a porous additive, wherein the conductive agent includes a high specific surface area conductive carbon black, and the specific surface area of ​​the conductive carbon black is ≥130m 2 / g.

[0026] For example, the specific surface area of ​​the conductive carbon black is 130 m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g, 170m 2 / g and above 130m 2 The value of / g is not limited to the listed values, and other values ​​not listed within the given range are also applicable.

[0027] According to the inventor's research, lithium iron phosphate, porous additives, and high specific surface carbon black correspond to large, medium, and small pore size distributions, respectively. Since the lithium iron phosphate particles are filled with medium-pore porous additives and small-pore high specific surface carbon black, a multi-level gradient pore structure can be formed inside the pole piece. This multi-level gradient pore structure can reduce the tortuosity of lithium ion transmission inside the pole piece, speed up the transmission speed of lithium ions in the pore structure and shorten the pore path length, thereby improving the fast charging performance of the battery. Correspondingly, the battery's cycle life and low-temperature discharge capability will also be improved.

[0028] Furthermore, according to the inventors' research, the use of lithium iron phosphate, porous additives, and high surface area carbon black can also effectively improve the electrolyte wettability of the electrode.

[0029] Specifically, the known permeability coefficient model formula is:

[0030]

[0031] In the formula, is the electrolyte permeability coefficient, is the connectivity of the components of the electrode, is the distance between the pores on the critical path inside the electrode, It is the length of the critical path of the electrode, which is positively correlated with the thickness and compaction density of the electrode.

[0032] Based on the permeability coefficient model formula, it can be seen that the key to improving the wettability of the electrode electrolyte is to increase the porosity of the electrode and the distance between the pores. The present invention can effectively reduce the distance between the pores of the electrode by filling medium and small pore diameter porous additives and high specific surface carbon black between lithium iron phosphate particles. , thereby improving the electrolyte's wettability to the electrode. It is worth noting that the pore size between the primary aggregates of high specific surface area carbon black is higher than that of conventional conductive agents, which can further improve the electrode's ability to absorb and retain liquid, thereby improving the electrode's electrolyte wettability.

[0033] In addition, according to the inventor's research, high specific surface area conductive carbon black, compared with conventional conductive agents, such as those with a specific surface area of ​​60m 2 / g of conductive carbon black has a smaller particle size and a larger specific surface area. This makes it easier for the conductive network formed inside the electrode to which high specific surface conductivity conductive carbon black is applied to reach the permeation threshold. Therefore, the application of a small amount of high specific surface carbon black can effectively improve the conductivity of the electrode, and correspondingly, a large amount of lithium iron phosphate can effectively increase the energy density of the battery.

[0034] Therefore, based on the above description, the combined use of lithium iron phosphate, porous additives, and high specific surface carbon black can effectively improve the overall performance of the battery.

[0035] In some embodiments, the conductive agent further includes carbon nanotubes compounded with conductive carbon black. The particle structure of the conductive carbon black and the tubular structure of the carbon nanotubes can form more conductive channels in the material, which can further accelerate the transmission of lithium ions, thereby improving the conductivity of the electrode and the performance of the battery. For example, the carbon nanotubes can be single-walled carbon nanotubes, multi-walled carbon nanotubes, etc.

[0036] In some embodiments, the conductive agent is a compound of high specific surface conductive carbon black and multi-walled carbon nanotubes, wherein the specific surface area of ​​the multi-walled carbon nanotubes is 230-420 m 2 / g, and the tube diameter is 7-11nm. The specific surface area of ​​multi-walled carbon nanotubes is, for example, 230m 2 / g, 270m 2 / g, 320m 2 / g, 390m 2 / g, 420m 2 / g, or any two of the above values ​​are selected to form a new range, and the value taken within the new range; the diameter of the multi-walled carbon nanotube is, for example, 7nm, 8nm, 9nm, 10nm, 11nm, or any two of the above values ​​are selected to form a new range, and the value taken within the new range.

[0037] In some embodiments, the high specific surface area conductive carbon black satisfies: tap density ≤ 0.05 g / cm3 In general, the tap density reflects the filling of the gaps in the particles during vibration. A low tap density of carbon black means better dispersion of the particles. Therefore, by limiting the tap density of conductive carbon black, it helps to form a more uniform conductive network inside the electrode, further improving battery performance.

[0038] For example, the tap density of the conductive carbon black is 0.05 g / cm 3 , 0.04g / cm 3 , 0.03g / cm 3 , 0.02g / cm 3 , 0.01g / cm 3 Less than or equal to 0.05g / cm 3 The numerical value is not limited to the numerical value listed, and other numerical values ​​not listed in the given range are also applicable. The conductive carbon black that meets the above conditions is a conductive carbon black with a high specific surface area.

[0039] In some embodiments, the average particle size of the primary structure of the high specific surface area conductive carbon black is 20-30 nm. The average particle size of the primary structure of the high specific surface area conductive carbon black is, for example, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, or any two of the above values ​​are selected to form a new range, and the value taken within the new range.

[0040] In some embodiments, the pore size of the high-specific surface conductive carbon black is 5 to 30 nm, and the average pore size of the high-specific surface conductive carbon black is 5 to 9 nm. The pore size of the high-specific surface conductive carbon black is, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, or any two of the above values ​​are selected to form a new range, and the values ​​taken within the new range. Correspondingly, the average pore size of the high-specific surface conductive carbon black is, for example, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, or any two of the above values ​​are selected to form a new range, and the values ​​taken within the new range.

[0041] In some embodiments, the primary structure particle size of the high specific surface area conductive carbon black satisfies 60≤D 50 ≤82nm, further screening of carbon black particle size. High specific surface area conductive carbon black particle size D 50 For example, it is 60nm, 64nm, 68nm, 72nm, 76nm, 80nm, 82nm, or any two of the aforementioned values ​​are selected to form a new range, and the value taken within the new range.

[0042] In some specific embodiments, the volume of the pores with a size of 5 to 30 nm measured by nitrogen desorption of the high specific surface area conductive carbon black used in the present invention is 0.4 to 1.2 cm 3 / g.

[0043] In some specific embodiments, in the high specific surface area conductive carbon black used in the present invention, the volume of pores with a size of 5 to 30 nm accounts for 88% to 94% of the total pore volume.

[0044] In some embodiments, the porous additive is porous alumina. Lithium iron phosphate, porous alumina, and high specific surface carbon cooperate with each other to form a multi-level gradient pore structure inside the pole piece, which reduces the tortuosity of lithium ion transmission inside the pole piece, speeds up the transmission speed of lithium ions in the pore structure and shortens the pore path length, thereby improving the fast charging performance of the battery.

[0045] In some embodiments, the porous additive is porous alumina, wherein the specific surface area of ​​the porous alumina is 320-360 m 2 / g, and has a pore size distribution of 30 to 150 nm. The specific surface area of ​​porous alumina is, for example, 320 m 2 / g, 330m 2 / g, 340m 2 / g, 350m 2 / g, 360m 2 / g, or any two of the aforementioned values ​​are selected to form a new range, and the value taken within the new range; the pore size distribution of porous alumina is, for example, 30nm, 50nm, 70nm, 90nm, 110nm, 130nm, 150nm, or any two of the aforementioned values ​​are selected to form a new range, and the value taken within the new range.

[0046] In some implementations, the primary particle size of the porous alumina is 80 nm ≤ D 50 ≤120nm. Primary particle size D of porous alumina 50 For example, it is 80nm, 90nm, 100nm, 110nm, 120nm, or any two of the above values ​​are selected to form a new range, and the value taken within the new range.

[0047] In some implementations, the average primary particle size of the porous alumina is 60 nm.

[0048] In a specific embodiment, the binder is polyvinylidene fluoride (PVDF).

[0049] In some embodiments, the primary particle size of the lithium iron phosphate main material is in the range of 280-340 nm, and the particle size of the lithium iron phosphate main material satisfies 2.8≤(D 90 -D 10 ) / D 50≤3.2. The primary particle size of the lithium iron phosphate main material is, for example, 280nm, 290nm, 300nm, 310nm, 320nm, 330nm, 340nm, or any two of the above values ​​are selected to form a new range, and the value taken within the new range; at the same time, the primary particle size of the lithium iron phosphate main material (D 90 -D 10 ) / D 50 For example, 2.8, 2.9, 3.0, 3.1, 3.2, or any two of the aforementioned values ​​are selected to form a new range, and the value taken within the new range.

[0050] Among them, D 10 Defined as the particle size distribution corresponding to 10% of the volume distribution of lithium iron phosphate, D 50 Defined as the volume median particle size of the lithium iron phosphate, D 90 It is defined as the particle size distribution corresponding to 90% of the volume distribution of lithium iron phosphate, where D 10 , D 50 , D 90 The unit is μm.

[0051] According to the inventor's research, D 50 It reflects the average size of lithium iron phosphate, which can determine the diffusion path of lithium ions in lithium iron phosphate particles and affect the specific surface area of ​​lithium iron phosphate particles. Therefore, it can directly affect the fast charging performance and cycle performance of lithium iron phosphate. 50 The lower the density, the shorter the lithium ion diffusion path, the lower the diffusion impedance of lithium iron phosphate and the larger the specific surface area. The low diffusion impedance of lithium iron phosphate is conducive to the rapid charging and discharging of lithium iron phosphate, but the large specific surface area of ​​lithium iron phosphate will lead to more side reactions with the electrolyte and reduced cycle performance. Therefore, screening out the appropriate size of lithium iron phosphate particles is the key to further optimizing the performance of the electrode.

[0052] In this embodiment, the effect of the particle size of lithium iron phosphate on the performance of the pole piece is taken into consideration, and the particle size of lithium iron phosphate is screened to make the lithium iron phosphate have a suitable density. While the lithium iron phosphate particles can be densely packed, a good pore distribution inside the pole piece can be ensured, so that the pole piece has the characteristics of high energy density, good electrolyte wettability and excellent fast charging performance.

[0053] A second aspect of the present invention provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode coating coated on the surface of the positive electrode current collector, wherein the positive electrode coating comprises any one of the positive electrode slurries in the above embodiments.

[0054] In the positive electrode sheet provided by the present invention, a conventional positive electrode current collector in the art may be used, for example, the positive electrode current collector includes carbon-coated aluminum foil.

[0055] When preparing the positive electrode sheet, for example, the positive electrode active material (lithium iron phosphate) of the present invention, the conductive agent (conductive carbon black with high specific surface area), the porous additive and the binder can be dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the positive electrode active layer includes 70-99wt% of the positive electrode active material, 0.5-15wt% of the conductive agent, 0.1-0.5wt% of the porous additive, and 0.5-15wt% of the binder according to the mass percentage, and further includes 80-98wt% of the positive electrode active material, 0.1-0.3wt% of the porous additive, 1-10wt% of the conductive agent, and 1-10wt% of the binder.

[0056] The third aspect of the present invention provides a lithium ion battery, wherein the positive electrode active material in the positive electrode sheet is lithium iron phosphate. It is conceivable that the lithium ion battery of the present invention includes a positive electrode sheet, an electrolyte and a separator in addition to the positive electrode sheet.

[0057] Generally, a battery includes an electrolyte, a battery cell, and a shell that encapsulates the battery cell. The electrolyte is injected into the battery cell in the shell. The battery cell includes a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet. The battery cell can be a laminated battery cell, that is, the battery cell is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet.

[0058] Specifically, the negative electrode sheet includes a negative electrode collector and a negative electrode coating located on at least one side surface of the negative electrode collector. Specifically, the negative electrode coating can be provided on one side surface of the negative electrode collector, or the negative electrode coating can be provided on both sides of the negative electrode collector in the thickness direction.

[0059] Specifically, the negative electrode coating (negative electrode active material layer) may include a negative electrode active material, a conductive agent and a binder, all of which may be conventional materials in the art. For example, the negative electrode active material may include at least one of graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloy), etc.; the conductive agent may include one or more of conductive carbon black, carbon nanotubes (CNT), acetylene black, graphene, Ketjen black, and carbon fiber; the binder may include one or more of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.

[0060] In the battery provided by the present invention, a conventional negative electrode current collector in the art may be used, for example, the negative electrode current collector includes copper foil.

[0061] In the battery provided by the present invention, the negative electrode sheet can be prepared by conventional methods in the art, for example, by a coating method. Specifically, the components used to form the negative electrode coating, such as the negative electrode active material, the conductive agent, the binder, etc., can be dispersed in a second solvent, the second solvent, for example, includes water, to prepare a negative electrode slurry, which is then coated on the surface of the negative electrode collector. After drying, rolling and other processes, the negative electrode sheet is obtained.

[0062] In the battery provided by the present invention, the electrolyte can be a conventional electrolyte in the art, for example, the electrolyte is a non-aqueous electrolyte, which specifically may include an organic solvent, an additive and an electrolyte salt, the organic solvent may include, for example, one or more of ethylene carbonate (EC), diethyl carbonate (DEC) and propylene carbonate (PC), the additive may include, for example, fluoroethylene carbonate (FEC), the electrolyte salt may include a lithium salt, the lithium salt may include, for example, lithium hexafluorophosphate (LiPF6), etc., but is not limited thereto.

[0063] In the battery provided by the present invention, the diaphragm is used to separate the positive electrode sheet and the negative electrode sheet to avoid short circuit between the positive electrode sheet and the negative electrode sheet. The embodiment of the present invention can adopt conventional diaphragms in the art, for example, polypropylene diaphragm (PP), polyethylene diaphragm (PE), polypropylene / polyethylene double-layer composite film (PP / PE), polyimide electrospinning diaphragm (PI), polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), cellulose non-woven fabric diaphragm, and diaphragm with ceramic coating, and the present invention is not limited to this.

[0064] In the embodiment of the present invention, the battery cell may be packaged with conventional shell materials in the art, and the shell may include, for example, soft packaging materials such as aluminum-plastic film, but is not limited thereto.

[0065] The present invention can assemble components such as positive electrode sheets, separators and negative electrode sheets into a battery by conventional methods in the art. For example, the positive electrode sheets, separators and negative electrode sheets can be stacked to produce a stacked battery cell; the battery cell is then placed in a shell (outer packaging), and after conventional processes such as liquid injection (i.e., injecting electrolyte) and packaging, the battery is produced.

[0066] The fourth aspect of the present invention provides an electric device, comprising the battery provided by the present invention. The present invention does not specifically limit the type of the electric device, and it can be any electric device including the battery, including but not limited to mobile phones, portable devices, laptop computers, electric bicycles, electric cars, electric toys, energy storage devices, etc.

[0067] In addition, in some embodiments, the improvement of the wettability of the battery electrolyte of the present invention can be evaluated by the voltage before the battery is formed, as follows:

[0068] The positive electrode sheet prepared by the present invention is matched with the graphite negative electrode to prepare a soft-pack laminated battery cell. When the battery is not charged or discharged, Li x FePO 4 x is close to 1, φc (V vs Li+ / Li) = 3.1V; while when graphite is not embedded with lithium, φa (V vs H+ / H) = 0V, that is, φa (V vs Li+ / Li) = 3.04V. Therefore, before the formation of LiFePO 4 / graphite battery voltage E = φc (VvsLi+ / Li) - φa (V vsLi+ / Li) = 0.06V. Due to the influence of process, materials, electrolyte, temperature, etc., the evaluation of LiFePO 4 / The standard for good electrolyte infiltration of graphite soft-pack batteries before formation is that the voltage before formation is not less than 100mV. Based on this, the present invention has the technical effect of improving the electrolyte wettability of the electrode.

[0069] The present invention is further described below through specific embodiments.

[0070] In order to ensure the battery energy density and fast charging performance, the average particle size of the lithium iron phosphate primary particles in the comparative example and the embodiment is preferably 300nm, (D 90 -D 10 ) / D 50 =3.0. The porous additive used in the comparative example and the embodiment is porous alumina; the binder is polyvinylidene fluoride (PVDF); the conductive agent is a compound of conductive carbon black and carbon nanotubes; the carbon black conductive agents are conventional carbon black SP-1, high specific surface area conductive carbon black SP-2 and SP-3, and the specific carbon black parameters are shown in Table 1.

[0071] Table 1

[0072]

[0073] In the above table, the pore size parameters, specific surface area, and tap density of carbon black are tested in the following way (porous alumina refers to the carbon black test method):

[0074] (1) The specific surface area and pore parameters of carbon black of different embodiments and comparative examples were tested according to the method of GB / T19587-2004. Specifically, the specific surface area and pore size distribution of carbon black were determined by nitrogen adsorption method. The sample was vacuum degassed at 250°C for 2 hours, and then the adsorption and desorption performance of the sample for N2 was measured in the range of p / p0 0~1 at liquid nitrogen (77K) temperature. The specific surface area of ​​carbon black was determined by multi-point Brunauer-Emmett-Teller (BET) method; the micropore area and micropore volume of the sample were analyzed by t-plot method; the pore size distribution of carbon black was calculated by density functional theory (DFT) method (N2@77K in carbon slit pore QSDFT adsorption branch model).

[0075] (2) Tap density test. Put the weighed powder into the measuring cylinder of the vibration device and fix the measuring cylinder on the support. Turn the cam, and the directional rod drives the support to slide up and down and hit the anvil. Vibrate 250±15 times per minute for 12 minutes. Measure the volume of the powder in the measuring cylinder. The ratio of the powder mass to the volume is the tap density of the powder.

[0076] Example 1

[0077] 1. Preparation of positive electrode:

[0078] The positive electrode formula of lithium iron phosphate, high specific surface area conductive carbon black SP-2, carbon nanotubes, porous alumina, and PVDF is 96.9:0.5:0.5:0.1:2 by mass ratio. First, lithium iron phosphate, high specific surface area conductive carbon black SP-2, porous alumina, and PVDF powder are added into a stirring tank and stirred at a low speed for 30 minutes to initially form a dispersed and uniform mixture.

[0079] Add N-methylpyrrolidone solution (NMP), set the slurry solid content at 72%, knead for 4 hours without dispersing, and form a first mixed solution;

[0080] Add carbon nanotubes and NMP to the first mixed solution, set the slurry solid content to 60%, and disperse at high speed for 2 hours to prepare a positive electrode slurry;

[0081] The positive electrode slurry is evenly coated on both sides of the carbon-coated aluminum foil, and then baked and dried, and then hot pressed and cut to obtain the positive electrode sheet;

[0082] Among them, the positive electrode slurry formula, mass percentage, lithium iron phosphate: high specific gravity carbon black SP-2: carbon nanotubes: porous alumina: PVDF = 96.9: 0.5: 0.5: 0.1: 2.

[0083] 2. Preparation of negative electrode sheet:

[0084] Negative electrode slurry formula, mass percentage, active material: conductive agent SP-1: CMC: SBR = 95.3: 1.5: 1.4: 1.8, slurry solid content 48%, the prepared negative electrode slurry is coated on the surface of copper foil, baked and dried to form a negative electrode material coating, and the prepared negative electrode sheets are rolled and cut.

[0085] 3. Preparation of electrolyte:

[0086] The electrolyte used in the soft pack battery is a mixed carbonate with a concentration of 1 mol / L lithium hexafluorophosphate (solvent ethylene carbonate (EC): diethyl carbonate (DEC), dimethyl carbonate (DMC) = 1:1:1)

[0087] 4. Diaphragm:

[0088] A commercially available conventional 12 μm porous polyethylene separator was used.

[0089] 5. Preparation of lithium secondary batteries:

[0090] The die-cut positive electrode sheet, negative electrode sheet and separator are stacked in order by using a stacking process to obtain a stacked core, which is then packaged in an aluminum-plastic bag, injected with electrolyte after drying, and subjected to processes such as infiltration, formation and capacity separation to obtain a lithium secondary battery.

[0091] Examples 2-12 and Comparative Examples 1-3, except for the change in the positive electrode formula, other conditions are the same as those of Example 1, and the specific differences are shown in Table 2.

[0092] Table 2

[0093]

[0094] The following performance tests were performed on the positive electrode sheets or batteries of each embodiment and comparative example, and the results are shown in Table 3.

[0095] (1) Diaphragm resistance test:

[0096] Take the negative electrode sheets prepared in the embodiments and comparative examples, 10 sheets (30 mm*50 mm) are taken from each batch, and a 2-probe sheet resistance meter is used to perform a sheet resistance test. Six values ​​are tested for each sheet and the average value is taken.

[0097] (2) Electrolyte wetting test:

[0098] The soft-pack batteries prepared in the embodiments and comparative examples were immersed in high temperature after liquid injection. Ten batteries in each group were immersed in 45°C for 24 hours, and the voltage of each battery cell was recorded, and the average voltage of the 10 batteries was taken. In addition, ten batteries in each group were immersed in 45°C for 48 hours, and the voltage of each battery cell was recorded, and the average voltage of the 10 batteries was taken.

[0099] (3) Cycle test:

[0100] In each group of the embodiments and comparative examples, three soft-pack cells after capacity division were taken, and charged and discharged for 2000 cycles with a current of 1C in the voltage range of 2.0-3.75V at room temperature (25°C). The average value of the capacity retention rate after 2000 cycles was taken for each group of cells.

[0101] (4) Low temperature discharge test:

[0102] For each group of the embodiments and comparative examples, three soft-pack cells after capacity division were taken, and they were fully charged to 3.75V at room temperature using a 1C constant current and constant voltage, and then the fully charged cells were transferred to a -20°C environment and placed for 4 hours, and finally discharged to 2.0V at a 0.33C constant current in a -20°C environment, the discharge capacity was recorded, and the -20°C low-temperature discharge capacity retention rate was calculated, and the average value of the three cells was taken.

[0103] (5) Dynamic performance DCR test

[0104] The soft-pack cells prepared in the embodiment and the comparative example were tested for DCR after the K value was measured. The main steps of the DCR test are as follows: (1) In the voltage range of 2.0-3.75V, the average capacity C1 was taken at 0.33C for three weeks; (2) 0.33C was charged to 50% SOC, left for 1h, and the voltage was recorded as V1; (3) 4C was charged for 10s and left for 40s, at which time the voltage was recorded as V2; (4) At room temperature, 0.33C was charged to the cut-off voltage of 3.75V and ended. Finally, the DCR of 50% SOC charging at 4C rate was obtained, DCR=(V2-V1) / 4 / C1.

[0105] Table 3

[0106]

[0107] From the data in Table 3, it can be seen that in Examples 1-5, as the proportion of high-specific carbon black SP-2 formula increases (from 0.5 to 0.9), the negative electrode film resistance gradually decreases, the battery voltage of the electrolyte 45°C / 24h high-temperature infiltration continues to rise, the cycle capacity retention rate and low-temperature discharge performance continue to improve, and the DCR continues to decrease. It can be seen that the increase in the proportion of high-specific conductive carbon black will gradually improve the electrolyte wettability of the electrode, the battery's fast charging ability, cycle life and low-temperature discharge ability, and the battery's rate performance is further improved.

[0108] It can be seen from Example 6 that when the amount of SP-2 added is increased to 1.0, the electrical performance of the battery is not further improved. SP-2 has a very high porosity and excellent conductivity, but when the amount of SP-2 added is greater than 0.9, its effect will reach the upper threshold limit and will no longer have a further improvement effect on the performance of the battery.

[0109] It can be seen from Example 5 (the amount of porous alumina added is 0.1) and Examples 7-8 that when the amount of porous alumina added is increased to 0.2 in Example 7, the battery 45°C / 24h infiltration voltage rises, the cycle capacity retention rate and low-temperature discharge performance are further improved, and the DCR decreases; and when the amount of porous alumina added is 0.3 in Example 8, the diaphragm resistance, cycle capacity retention rate, and low-temperature discharge performance all begin to deteriorate, and there is no significant improvement in DCR. It can be seen that appropriately increasing the amount of porous alumina can further improve the electrical performance of the battery, but when the amount of porous alumina added is too much, its effect will deteriorate. Specifically, because porous alumina has a high specific surface area of ​​350m2 / g and a pore size distribution of 30-150nm, it is difficult to disperse in the slurry. If the amount added is too high, it will affect the dispersion consistency and stability of the slurry, resulting in uneven dispersion of the components of the formula and low consistency of the pole pieces made, which in turn leads to poor electrical performance of the battery.

[0110] It can be seen from Examples 9-12 (using SP-2) and Examples 1-4 (using SP-3) that the use of higher specific surface carbon black SP-3 can further improve the battery's fast charging capability, cycle capacity retention rate and low temperature performance. Among them, in Examples 9-11, as the proportion of electrical carbon black increases, the battery performance is further improved; when the addition amount of SP-3 in Example 12 is 0.8, the electrical performance deteriorates to a certain extent. It can be seen that high specific surface carbon black has a smaller particle size, higher specific surface, and higher porosity, which helps to improve the conductivity and wettability of the electrode, but if the specific surface is too large, it will cause the existing slurry process to be unable to disperse, and its role cannot be fully exerted. On the contrary, it will cause the electrical performance to deteriorate due to uneven dispersion. Therefore, the selection of high specific surface carbon black should be carried out on the premise of meeting the existing process technology to achieve the improvement of electrical performance.

[0111] According to Example 11 (the amount of porous alumina added is 0.1) and Examples 13-14, it can be seen that high specific surface area carbon black compounded with porous alumina can effectively improve the wettability of the positive electrode, cycle capacity retention rate and low temperature performance, and has higher rate performance. Among them, in Example 13, the amount of porous alumina added is 0.2, and the increase in its proportion further improves the performance improvement effect. However, when the amount of porous alumina added in Example 14 reaches 0.3, the porous alumina with a high specific surface area also affects the dispersion consistency and stability of the slurry, resulting in uneven dispersion of the components of the formula and low consistency of the produced electrode, which in turn leads to poor battery electrical performance.

[0112] The carbon black in Comparative Example 1 is SP-1; Comparative Example 2 is a compound of SP-1 and 0.2 porous alumina. Compared with Comparative Example 1, the battery test effect of Comparative Example 2 with porous alumina added is significantly improved, which once again confirms the improvement of porous alumina on the electrolyte wettability of the electrode, the battery fast charging ability, the cycle capacity retention rate and the low temperature performance. In addition, compared with Example 7 (SP-2 and 0.2 porous alumina compound), Comparative Example 2 has high negative electrode membrane resistance, low battery voltage at 45°C / 24h high temperature infiltration of electrolyte, low cycle capacity retention rate and low temperature discharge performance, and high DCR. It can be seen that high-specific surface area conductive carbon black can greatly improve the comprehensive performance of the battery, including the electrolyte wettability of the electrode, and improve the battery's fast charging ability, cycle life and low temperature discharge ability.

[0113] In addition, Comparative Example 3 and Example 1, and Comparative Example 4 and Example 9 can also confirm the improvement effect of porous alumina on the electrolyte wettability of the electrode, the battery fast charging capability, the cycle capacity retention rate and the low temperature performance.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode slurry, characterized in that: The positive electrode slurry comprises: a lithium iron phosphate main material, a binder, a conductive agent and a porous additive; Wherein, the conductive agent comprises conductive carbon black with a high specific surface area, and the specific surface area of ​​the conductive carbon black is ≥130m 2 / g.

2. The positive electrode slurry according to claim 1, characterized in that The conductive agent also includes carbon nanotubes compounded with the conductive carbon black.

3. The positive electrode slurry according to claim 2, characterized in that The carbon nanotubes are multi-walled carbon nanotubes, and the specific surface area of ​​the multi-walled carbon nanotubes is 230-420 m 2 / g, tube diameter is 7~11nm.

4. The positive electrode slurry according to claim 1, characterized in that: The tap density of the conductive carbon black is ≤0.05 g / cm 3 .

5. The positive electrode slurry according to claim 4, characterized in that: The average particle size of the primary structure of the conductive carbon black is 20-30 nm.

6. The positive electrode slurry according to any one of claims 1 to 5, characterized in that: The porous additive is porous alumina.

7. The positive electrode slurry according to claim 6, characterized in that: The specific surface area of ​​the porous alumina is 320-360 m 2 / g, and the porous alumina has a pore size distribution of 30-150 nm.

8. The positive electrode slurry according to claim 7, characterized in that: The primary particle size of the porous alumina is 80nm≤D 50 ≤120nm.

9. The positive electrode slurry according to claim 7 or 8, characterized in that: The average primary particle size of the porous alumina is 60 nm.

10. The positive electrode slurry according to any one of claims 1 to 5, characterized in that: The primary particle size of the lithium iron phosphate main material is in the range of 280-340 nm, and the particle size of the lithium iron phosphate main material satisfies 2.8≤(D 90 -D 10 ) / D 50 ≤3.

2.

11. The positive electrode slurry according to any one of claims 1 to 5, characterized in that: The binder is polyvinylidene fluoride.

12. The positive electrode slurry according to any one of claims 1 to 5, characterized in that: The pore size of the conductive carbon black is 5-30 nm, and the average pore size of the conductive carbon black is 5-9 nm.

13. The positive electrode slurry according to any one of claims 1 to 5, characterized in that: The primary structure particle size of the conductive carbon black is 60≤D 50 ≤82nm.

14. A positive electrode sheet, characterized in that: include: A positive electrode current collector and a positive electrode coating coated on the surface of the positive electrode current collector, wherein the positive electrode coating comprises the positive electrode slurry according to any one of claims 1 to 13.

15. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 14.

16. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 15.

Citation Information

Cited By

  • High-rate long-cycle lithium iron phosphate battery and preparation method thereof

    CN120878995A

  • Binder and method for producing same, lithium iron phosphate cathode and method for producing same, lithium ion battery

    CN122587634A

  • Positive electrode slurry, lithium-ion battery, and electric device

    WO2026123617A1